2021
DOI: 10.48550/arxiv.2111.11282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arecibo observations of a burst storm from FRB 20121102A in 2016

Abstract: FRB 20121102A is the first known fast radio burst (FRB) from which repeat bursts were detected, and one of the best-studied FRB sources in the literature. Here we report on the analysis of 478 bursts from FRB 20121102A using the 305-m Arecibo telescope, detected during approximately 59 hours of observations between December 2015 and October 2016. The majority of bursts are from a burst storm around September 2016. This is the earliest available sample of a large number of FRB 20121102A bursts, and it thus prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 70 publications
(136 reference statements)
5
16
0
Order By: Relevance
“…The largest numbers of bursts were found with the Arecibo telescope and the Five-hundred-meter Aperture Spherical radio Telescope (FAST). Hewitt et al (2021) reported a total of 478 bursts in 59 hours of observations with the Arecibo telescope through 2016 and an activity peak in September (a subset of which was previously found by Gourdji et al (2019) and Aggarwal et al (2021)). Li et al (2021b) reported 1652 bursts in 59.5 observing hours with FAST in September and October 2019, triggered when the source was known to be active.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…The largest numbers of bursts were found with the Arecibo telescope and the Five-hundred-meter Aperture Spherical radio Telescope (FAST). Hewitt et al (2021) reported a total of 478 bursts in 59 hours of observations with the Arecibo telescope through 2016 and an activity peak in September (a subset of which was previously found by Gourdji et al (2019) and Aggarwal et al (2021)). Li et al (2021b) reported 1652 bursts in 59.5 observing hours with FAST in September and October 2019, triggered when the source was known to be active.…”
Section: Introductionmentioning
confidence: 69%
“…We made major changes to the pipeline that was used for previous searches (Gourdji et al 2019;Hewitt et al 2021) and which has been described in detail in Michilli et al (2018a). To save disk space and speed up the search the data was converted to total intensity and downsampled in time by a factor of 8 to a resolution of 81.92 µs using psrfits_subband 3 .…”
Section: Observations and Searchmentioning
confidence: 99%
See 3 more Smart Citations